1984
DOI: 10.1021/jo00190a021
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Diels-Alder reactivity of several new chalcogen-halogen substituted butadienes

Abstract: Addition of halogens and pseudohalogens across one -bond of l,4-dichlorobut-2-yne, followed by a 1,4elimination, is an efficient synthesis of several new polysubstituted butadienes. If the product dienes have a sulfur or selenium substitutent they are quite reactive, undergoing cycloaddition with the moderately reactive dienophile methyl vinyl ketone at 20 °C in the presence of boron trifluoride etherate. The regiochemistry of the cycloadditions was elucidated, and the limitations of the methodology are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Commercially available Br-Se-C 6 H 5 and Te 2 (C 6 H 5 ) 2 (SigmaAldrich) were employed without further purification. BrTe-C 6 H 5 [18] was obtained according to a procedure reported for the synthesis of the corresponding selenium derivative [12,19]: Diphenylditelluride was dissolved in 20 ml of CHCl 3 , cooled to 0°C and treated with the stoichiometric quantity of elemental bromine dissolved in the same solvent. After stirring for 1 h at 0°C the solvent was removed in vacuum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercially available Br-Se-C 6 H 5 and Te 2 (C 6 H 5 ) 2 (SigmaAldrich) were employed without further purification. BrTe-C 6 H 5 [18] was obtained according to a procedure reported for the synthesis of the corresponding selenium derivative [12,19]: Diphenylditelluride was dissolved in 20 ml of CHCl 3 , cooled to 0°C and treated with the stoichiometric quantity of elemental bromine dissolved in the same solvent. After stirring for 1 h at 0°C the solvent was removed in vacuum.…”
Section: Methodsmentioning
confidence: 99%
“…The corresponding sulphur bromide starting compound, Br-S-C 6 H 5 , is reported to be relatively unstable [12]. We tried to generate it on a route similar to that one given in the Experimental Section for the synthesis of Br-Te-C 6 H 5 by the reaction of diphenyldisulphide with elemental bromine.…”
Section: Introductionmentioning
confidence: 99%
“…[37,38] Sulfoxides 8b؊c were prepared by employing this protocol; the trans mode of addition arises from the reactions of sulfenyl chlorides with alkynes. [39] Chemoselective protiodesilylation of 8a؊c was readily achieved and furnished sulfoxides 9a؊c. It was found that performing the addition of 5 to trimethylsilylacetylene at higher temperature preferentially yielded the opposite geometric isomer 8d.…”
Section: -Alkenesulfinyl Chloridesmentioning
confidence: 99%
“…1 Dienes that contain sulfur or oxygen substituent show a greater reactivity. 2 Chemical literature contains many examples of attempts to prepare substituted butadienes. [3][4][5][6][7][8][9] It is known from the US-Patent 10 that some tetrakis(thio)substituted butadienes and some thiols 11 have biological activities such as fungicidal, insecticidal, herbicidal and nematocidal.…”
Section: Introductionmentioning
confidence: 99%